Differential synovial Th1 cell reactivity towards Escherichia coli antigens in patients with ankylosing spondylitis and rheumatoid arthritis. Issue 9 (26th June 2012) - Syrbe, Uta; Scheer, Rebecca; Wu, Peihua; Sieper, Joachim
Abstract : Objective: Ankylosing spondylitis (AS) is associated with clinical and subclinical mucosal inflammation, suggesting that commensal bacteria contribute to the pathogenesis of the disease. Methods: The frequency of Th1 cells reacting towards conserved Escherichia coli ( E coli ) proteins and pathogenicity factors in peripheral blood mononuclear cells (PBMNC) and synovial fluid mononuclear cells (SFMNC) of patients with AS and those with rheumatoid arthritis (RA) was determined. PBMNC from healthy individuals were included as controls. Results: Higher frequencies of Th1 cells reacting to conserved E coli proteins were observed in SFMNC and, to a lesser extent, in PBMNC of patients with AS compared with patients with RA (SFMNC, p<0.01; PBMNC, p<0.05). In contrast, the frequencies of cytomegalovirus- and staphylococcal enterotoxin B (SEB)-induced Th1 cells did not differ between patients with AS and those with RA in SFMNC, and SEB-induced Th1 cell frequencies in PBMNCs were even higher in patients with RA than in those with AS (p<0.05). Conclusions: The high frequency and enrichment of E coli -specific CD4 T cells in the inflamed joints of patients with AS but not those with RA suggests that commensal bacteria are relevant antigens in AS that might trigger the disease.